38-3x=-7(6+5x)-8x

Simple and best practice solution for 38-3x=-7(6+5x)-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 38-3x=-7(6+5x)-8x equation:



38-3x=-7(6+5x)-8x
We move all terms to the left:
38-3x-(-7(6+5x)-8x)=0
We add all the numbers together, and all the variables
-3x-(-7(5x+6)-8x)+38=0
We calculate terms in parentheses: -(-7(5x+6)-8x), so:
-7(5x+6)-8x
We add all the numbers together, and all the variables
-8x-7(5x+6)
We multiply parentheses
-8x-35x-42
We add all the numbers together, and all the variables
-43x-42
Back to the equation:
-(-43x-42)
We get rid of parentheses
-3x+43x+42+38=0
We add all the numbers together, and all the variables
40x+80=0
We move all terms containing x to the left, all other terms to the right
40x=-80
x=-80/40
x=-2

See similar equations:

| -5(6t+1)=205 | | 2x+5=2x+7 | | 15x=-15x-60 | | (3x-2)/5=4 | | -4(2m+26)=-16(m+4) | | 4(-3v+7)=-2v+38 | | 13*87=x | | 5(x-3)-12=8 | | |3x+4|=|2x-4| | | -2(11b-3)b=5 | | 60=4(9+p) | | 7(2x-4)=3(4x+2) | | 11x-21+8x=15 | | 66=4(2y-1.5) | | 2x​​+5=4x+9 | | 9p-2=10p-2 | | (4b+7)−(6b−3)=- | | a-5/10-2a=-3/5 | | 2x+35+5x=22 | | -12-3(7x+6)=33 | | 5k+2(11-k)=-5 | | 2(7x+2/3)=14x+4/3 | | x*55=33 | | -16-2b+6b÷2=b | | 7t+9=8t | | -2(4x-1)=5x(x+3) | | 3(8x-6)=-66 | | F(5)=6x+7 | | 4(2x+3)=2(3x+10) | | (x)=6x+7 | | 8x=11x-16 | | 5(3x+11)=175 |

Equations solver categories